2002
DOI: 10.1097/00126334-200204010-00003
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Hepatotoxicity Associated With Nonnucleoside Reverse Transcriptase Inhibitors

Abstract: Nonnucleoside reverse transcriptase inhibitors (NNRTIs), particularly nevirapine, have been associated with hepatotoxicity. We performed a retrospective study to determine the incidence of NNRTI hepatotoxicity in a group of HIV-infected patients from a New York City practice. These patients are predominantly homosexual white males. We also analyzed the effect of coinfection with hepatitis B (HBV) or hepatitis C (HCV) virus. In total, 272 patients received NNRTIS: 40 (15%) received delavirdine, 91 (33%) receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(23 citation statements)
references
References 11 publications
3
19
1
Order By: Relevance
“…The significance of the ␥-GT increase remains obscure, but it has been hypothesized to represent a marker of microsomial induction rather than a liver damage sign. As in other studies [19,22,23], our HIV and HCV/HBV co-infected patients have not shown significant increase of ALT and AST levels. The 8-years follow-up highlights that liver enzyme levels of HBV/HCV and HIV co-infected patients are similar with those of patients without hepatitis, in spite of higher baseline levels.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The significance of the ␥-GT increase remains obscure, but it has been hypothesized to represent a marker of microsomial induction rather than a liver damage sign. As in other studies [19,22,23], our HIV and HCV/HBV co-infected patients have not shown significant increase of ALT and AST levels. The 8-years follow-up highlights that liver enzyme levels of HBV/HCV and HIV co-infected patients are similar with those of patients without hepatitis, in spite of higher baseline levels.…”
Section: Discussionsupporting
confidence: 84%
“…In collusion with other studies [1,18,19], we have observed that NVP-treatment causes more often the increase of ␥-GT than ALT and AST: after two years, ␥-GT levels reached a plateau in patients without hepatitis. This trend has been pointed out also by the Murphy et al meta-analysis [19].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In some series, the incidence of liver toxicity is not higher compared to other antiretrovirals [41,43,44]. This is especially true in populations with a low prevalence of chronic HCV infection [43].…”
Section: Non-nucleoside Analogues Reverse Transcriptase Inhibitorsmentioning
confidence: 98%
“…64,83 Overall, however, NNRTIs have a low rate of clinically significant hepatotoxicity. 84,85 Among PIs, ritonavir and ritonavir-boosted HAART regimens have been most studied and identified as independent risk factors for the development of hepatotoxicity. Wit and colleagues 86 documented ritonavir (full-dose therapy) as an independent risk factor, with a 5.8-fold increased risk of developing grade 4 liver enzyme elevations.…”
Section: Drug-induced Liver Injurymentioning
confidence: 99%